Norm Contestation, Robustness, and Replacement. Issue 1 (20th February 2019) - Sandholtz, Wayne
Abstract: The collaborative project reported in this special issue has sought to move beyond any straightforward connection between norm violation or norm contestation, on the one hand, and norm robustness on the other. Instead, the effects of contestation on norm robustness are conditioned by characteristics of norm challengers and norm defenders, by the nature of the contestation, and by features of norm institutionalization and embeddedness. This contribution assesses the case studies in light of the framing conjectures. It draws broad conclusions, indicates areas where general conclusions are not yet possible, and points out directions for further theoretical development and empirical investigation.